#DomesticViolence During the COVID-19 Global Pandemic: An Analysis of Public Commentary via Twitter. (July 2022) - López, Gabriela; Bogen, Katherine W; Meza-Lopez, Richard J; Nugent, Nicole R; Orchowski, Lindsay M
The current study sought to characterize commentary regarding intimate partner violence during the COVID-19 (SARS-CoV-2) pandemic via the Twitter hashtags #DomesticAbuse and #DomesticViolence. A sample of 481 original, English-language tweets containing the hashtag #DomesticAbuse or #DomesticViolence posted across five consecutive weekdays from March 22 to March 27, 2020—during which many places were enacting lockdown mandates—was examined using thematic content analyses. Overall, Twitter users commented on potential increased rates of IPV, while adding details about abuse tactics that could be employed by perpetrators during the pandemic. Additionally, Twitter users disclosed personal experiences of IPV victimization. Four themes were identified, including (1) type of domestic violence (i.e. whether the violence was COVID-specific or general domestic violence), (2) commentary about IPV (i.e. general reflections, decentralizing and centralizing survivorhood), (3) perpetrator tactic (i.e. abuse tactic used by the perpetrator), and (4) institutions responsible (i.e. institutions responsible for providing services to survivors). Overall, the commentary on Twitter reflected an effort to raise awareness and share informational aid for potential victims/survivors of IPV. Data highlight the potential of social media networks in conveniently facilitating the sharing and spreading of useful resources to other users. Future research should examine whether resources shared via Twitter reach individuals who need them and empower individuals to garner support.